Crown of Thorns Starfish (Achantaster planci) Meal in Formulated Diets on the Growth of Whiteleg Prawn (Penaeus vannamei Boone, 1931) - Safir, Muhammad; Izhar, Izhar; Mangitung, Seftina Fifi; Serdiati, Novalina; Nur’aidah, Nur’aidah (Department of Aquaculture, 2025)
The study was conducted to investigate the growth of juvenile whiteleg prawn (Penaeus vannamei) fed with different doses of the crown of thorns starfish (Acanthaster planci) meal in formulated diets. The study was designed using a completely randomized design consisting of four treatments and three replications. The treatments were the dosages of A. planci meal in a formulated diet, namely A: 0% (control); B: 9%; C: 18%; and D: 27%. Juveniles of P. vannamei were reared in a 40 × 25 × 25 cm3 aquarium (15 Liter water volume) for 28 days. The results showed that the Individual Weight Gain (IWG) of juveniles ranged from 2.68 to 2.94 g, Specific Growth Rate (SGR) ranged from 2.82 to 2.93% day-1, feed conversion ratio ranged from 3.03-3.22, feed efficiency was 31.31-33.17%, and survival rate was 96.67-100%. The analysis of variance revealed that the use of A. planci meal in a formulated diet did not have a significant effect (p>0.05) on growth performance (IWG and SGR), feed conversion ratio, feed efficiency and survival rate of juveniles of whiteleg prawn during 28 days of culture. The utilization of A. planci meal up to a dose of 27% can be used as a substitute for fishmeal as a source of feed protein for cultured whiteleg prawns.